Assessment of Radiofrequency Radiation Distribution around Mobile Base Stations in Makurdi, Benue State - Iortile, J.T; Agba, E.H (International Journal of Natural Sciences Research, 2014)
The radiofrequency field levels of selected MTN and ZAIN base stations in Makurdi were measured using electromagnetic field tester (EMF 827, Lutron). Measurements were done at distances of approximately 5.00, 10.00, 15.00 and 20.00 metres for each base station at the North, South, West, and East directions. Results shows that the average magnetic field levels of MTN and ZAIN base station ranged between 0.09 μT to 0.15 μT. The mean electric field values for eye, brain and muscles ranged between 18.81〖vm〗^(-1)to 31.55〖vm〗^(-1). The specific absorption rate (SAR) were found to range between 0.18〖Wkg〗^(-1)to 1.03〖Wkg〗^(-1) for MTN and ZAIN networks. This work has, therefore shown that the radiation emitted by the mobile base stations are within the regulatory standards and have no adverse effects to the members of the public.